Hubungan antara Kecerdasan Emosional dan Adaptabilitas Karier Siswa Sekolah Menengah Kejuruan (SMK) “X” di Kota Salatiga - Zania Timur Maulidina; Doddy Hendro Wibowo (Universitas Kristen Maranatha, 2021)
Students need to prepare themselves for their desired career. This study aims to determine the relationship between emotional intelligence and career adaptability among vocational students. This study used a sample of 66 students of SMK